Comparative Analysis of Sensory, Chemical, and Microbiological Properties of Dadih from Different Regions in West Sumatra, Indonesia - Habibi, Nur Ahmad; Gusnedi, Gusnedi; Edmon, Edmon; Utami, Citra Tristi; Darwel, Darwel (Poltekita: Jurnal Ilmu Kesehatan, 2025)
Background: Dadih, a traditional fermented buffalo milk from West Sumatra, Indonesia, varies in quality depending on its production region. This study aimed to compare the sensory, chemical, and microbiological properties of Dadih, a traditional fermented buffalo milk, from different regions of West Sumatra, Indonesia, to identify quality variations and their potential determinants. Method: Samples were collected from Payakumbuh, Batusangkar, Bukittinggi, and Alahan Panjang. Sensory evaluation assessed taste, aroma, color, and texture; chemical analysis measured pH and protein content; and microbiological analysis determined total lactic acid bacteria (LAB) counts. Results: Sensory results showed significant differences in texture (p=0.004) and aroma (p<0.001), with Payakumbuh samples scoring highest in these parameters. Chemical analysis revealed Payakumbuh Dadih had the lowest pH (4.60 ± 0.32) and highest protein content (8.91 ± 0.22%). The highest LAB count was found in Batusangkar samples (9.3 × 10⁸ CFU/g). Conclusion: The study concluded that Dadih in West Sumatra exhibited diverse properties influenced by regional processing practices, hygiene, and raw material sources. These findings provide a basis for improving production techniques to enhance sensory quality, nutritional value, and functional food potential.